Cyberloafing to Escape From the “Devil”: Investigating the Impact of Abusive Supervision From the Third-Party Perspective - Liang, Xuedong; Guo, Gengxuan; Gong, Qunxi; Li, Sipan; Li, Ziyang (Frontiers in Psychology, 2022)
Purpose: Previous studies on cyberloafing focus on individual and organization factors, ignoring the situation of employees as the event observers. Drawing on affective events theory, present study proposed a theoretical model for the relationships between peer abusive supervision, negative affectivity, cyberloafing and hostile attribute bias, which aims to bridge the above research gap. Methodology: Multi-wave data of 355 employees from 8 service-oriented companies in Southwest China supported our model. Time-lag method and Critical incident techniques were introduced during the data collection stage. OLS regression and Bootstrapping method were employed for hypothesis test. Findings: The empirical results indicated that peer abusive supervision was positively related to third-party’s cyberloafing, the third-party’s negative affectivity plays a mediating role among above relationships. In addition, the third-party’s hostile attribution bias moderated the mediating role of third-party’s negative affectivity. Specifically, the effect of peer abusive supervision on third-party’s negative affectivity and the mediating effect of his negative affectivity were stronger when the third-party’s hostile attribution bias was higher. Originality: Drawing on affective events theory, current study constructed a process model of third-party’s cyberloafing reactions to peer abusive supervision, which helps explain the affective mechanism and the boundary conditions of the above “events-affectivity-behavior” path. Our model is a positive response to previous scholars’ calls for research of abusive supervision from multiple perspectives. Meanwhile, current study explored the antecedent variable of cyberloafing from the perspective of event observers, which provides a theoretical basis for follow-up related research. Thirdly, this study further expanded the theoretical boundaries of affective events theory. Key words: peer abusive supervision, negative affectivity, cyberloafing, hostile attribution bias